ERUPTIONS AT BEZYMYANNYI IN 1993-1995 - Belousov A.B.; Firstov P.P.; Zhdanova E.Y. (My University, 1999)
Data on pyroclastic deposits, visual observations, and seismicity were used to reconstruct the sequence of eruptive events at Bezymyannyi in 1993. The eruption consisted of three episodes of block-and-ash pyroclastic flows which traveled for distances of 7, 8, and 5 km, respectively. The eruption column rose to a height of 13 km. The second episode of pyroclastic flows was accompanied by a partial collapse of the dome 0.006 km 3 in volume. A powerful vertical explosion and a lava flow occurred at the end of the eruption. The explosion deposited dense andesite lapilli over an area > 50 km SE of the volcano. The total volume of the erupted material was 0.07 km 3 . A brief description is given of the subsequent volcanic activity till September 1995: lava flowed episodically, no significant explosions took place.